2021
DOI: 10.21608/aimj.2021.79536.1495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidative stress in semen, follicular fluid and embryo culture medium on the outcome of assisted reproduction

Abstract: Background: Although many advances have been made in the field of assisted reproduction, the clinical outcomes remain less than desirable. Oxidative stress has been recently blamed on both male and female partners. Aim of the study: This work aimed to study the effect of oxidative stress in semen, follicular fluid, and embryo culture medium on the outcome of assisted reproduction. Patients and Methods: Fifty couples with unexplained infertility were subjected to a combined treatment of IVF and ICSI. Oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In infertile men, the increased levels of seminal lipid peroxides/MDA negatively correlated with normal spermatozoa morphology, vitality, seminal antioxidants, and fertilization rate (Agarwal et al, 2014a). In native semen samples and culture media of oocytes and embryos, the increased values of oxidative-reduction potentials (ORP) were negatively correlated with fertilizing capacity, excellent embryos transfer, and pregnancy rate (Sallam et al, 2021). In infertile men, the elevated levels of seminal ROS production, lipids peroxidation, and DNA fragmentation index markedly attenuated conventional and functional semen parameters including sperm concentration, total count, progressive motility, normal morphology, and antioxidant capacity compared to fertile men group (Mayorga-Torres et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In infertile men, the increased levels of seminal lipid peroxides/MDA negatively correlated with normal spermatozoa morphology, vitality, seminal antioxidants, and fertilization rate (Agarwal et al, 2014a). In native semen samples and culture media of oocytes and embryos, the increased values of oxidative-reduction potentials (ORP) were negatively correlated with fertilizing capacity, excellent embryos transfer, and pregnancy rate (Sallam et al, 2021). In infertile men, the elevated levels of seminal ROS production, lipids peroxidation, and DNA fragmentation index markedly attenuated conventional and functional semen parameters including sperm concentration, total count, progressive motility, normal morphology, and antioxidant capacity compared to fertile men group (Mayorga-Torres et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Another system for measuring oxidative stress incorporates electrochemical technology to calculate the static oxidative-reduction potential (ORP) in millivolts (mV) [150]. Sallam et al [152] demonstrated that the ORP levels in the culture medium of fertilized oocytes were lower than those of unfertilized oocytes. Similarly, the ORP levels measured in the culture medium of embryos that resulted in pregnancy were lower than those of embryos that did not lead to pregnancy.…”
Section: ) Measurement Of Oxidative Stress In the Ecmsmentioning
confidence: 99%
“…One potential limitation is that measurements are temperature sensitive (2–37 °C) with levels significantly increasing outside of this range [ 47 ]. While the MiOXSYS System™ has been evaluated in a number of large cohorts of infertile men, we could find only one published study to date (50 idiopathic infertile couples) that extended their analysis to evaluate fertilization and pregnancy outcomes, finding a cut off sORPmV < 1.57 mV/10 6 /mL predictive of fertilization and < 0.75 mV/10 6 /mL for clinical pregnancy [ 52 ]. Further large-scale cohort studies extending their analysis into pregnancy and live birth outcomes are still needed to determine the clinical utility of using MiOXSYS™ for ART.…”
Section: Current Clinical Measures Of Ros In Semenmentioning
confidence: 99%